The GLP-1R Agonist Exendin-4 Attenuates Hyperglycemia-Induced Chemoresistance in Human Endometrial Cancer Cells Through ROS-Mediated Mitochondrial Pathway - Zhang, Yu; Cheng, Juan; Li, Jing; He, Junxian; Li, Xiaomao; Xu, Fen (Frontiers in Oncology, 2021)
This study aimed to assess the effects of the antidiabetic drug Exendin-4 (Exe-4), a GLP-1 receptor agonist, on the response of human endometrial cancer cells to chemotherapy under high glucose (HG) conditions. Cell viability was detected using a cell counting kit (CCK)-8. Cell apoptosis and reactive oxygen species (ROS) levels were measured by flow cytometry. Gene expression was evaluated by real-time PCR and immunoblotting. The chemotherapeutic drug cisplatin (DDP) dose-dependently inhibited both human endometrial adenocarcinoma Ishikawa and HEC1B cells, a response reversed by HG. Meanwhile, Exe-4 attenuated hyperglycemia’s effect by elevating intracellular lactate dehydrogenase (LDH) and ROS production. Similarly, DDP-induced elevation of intracellular rhodamine123 was attenuated by HG, and Exe-4 reversed HG’s impact. The chemoresistance genes multidrug resistance-associated protein 1 (MRP1) and P-glycoprotein (Pgp) were upregulated. At the same time, topoisomerase II (TOPO II) was downregulated under HG conditions, suggesting HG-induced chemoresistance. Exe-4 did not significantly influence the above genes. DDP downregulated Bcl-2 and Bcl-XL and upregulated Bax, cytosolic cytochrome c, and PARP under normal glucose (NG) versus HG conditions, and Exe-4 attenuated these effects. Upstream of Bax/Bcl, acetylated P53 was upregulated by DDP and downregulated by HG, whose effect was reversed by Exe-4. DPP treatment significantly induced apoptosis and cell cycle arrest in the S phase under NG, and HG reduced these effects. Prolonged exposure to HG induces DDP chemoresistance in human endometrial cancer cells but is alleviated by Exe-4.